Control Algorithms for Matrix Converters With Low Mathematical Complexity - Igney, Jens; Hahn, Ingo (21st International Symposium on Power Electronics (Ee), 2021)
Due to the degrees of freedom inherent in matrix converter modulation, there are a large number of different, seemingly contradictory modulation strategies. This work contributes to a systematization of at least a subset of the strategies. For this purpose, a systematic derivation of direct control algorithms is performed. "Direct" is meant in the sense that the duty cycles are computed using only basic arithmetic. Since such algorithms do not invoke mathematical library functions, they can be easily implemented in embedded processors or programmable logic.Due to their direct computability and systematic derivation from theory, the algorithms can be regarded as archetypes of matrix converter modulation and can be a valuable aid in comparing different control algorithms.
Keywords: Systematics; Program processors; Modulation; Power electronics; Libraries; Complexity theory; Classification algorithms; Matrix converters; Algorithm; Classification